Philippians - Holloway, Paul A., 1955- (Book collections on Project MUSE., 2017)
Paul's letter to the Philippians offers treasures to the reader--and historical and theological puzzles as well. Paul A. Holloway treats the letter as a literary unity and a letter of consolation, according to Greek and Roman understandings of that genre, written probably in Rome and thus the latest of Paul's letters to come down to us. Adapting the methodology of what he calls a new history of religions perspective, Holloway attends carefully to the religious topoi of Philippians, especially the metamorphic myth in chapter 2, and draws significant conclusions about Paul's personalism and "mysticism." With succinct and judicious excursuses treating pertinent exegetical and theological issues throughout, Holloway draws richly on Jewish, Greek, and Roman comparative material to present a complex understanding of the apostle as a Hellenized and Romanized Jew. --